Teachers on Trial : Values, Standards, and Equity in Judging Conduct and Competence - Gross, James A., 1933- (Book collections on Project MUSE., 1988)
Teachers on Trial is a study of 260 case decisions in New York State which tenured teachers were charged with incompetence or conduct unbecoming a professional. The author analyzes what, in the deciders' opinion, constituted conduct unbecoming and incompetence and critiques the standards used in making determinations.